INFEKSI CACING USUS YANG DITULARKAN MELALUI TANAH PADA ANAK SEKOLAH DASAR DI PERKOTAAN DAN PEDESAAN DI WILAYAH KERJA PUSKESMAS UNGARAN I - Sayono . . (Universitas Muhammadiyah Semarang, 2003)
ABSTRAKSI Background: Soil Transmitted Helminthes (STH) consist of Ascaris lumbtricoides, Trichuris trichiura, Necalor americanus, Ancylostoma duodenale, and Strogiloides stercoralis. These species grow well in Indonesia because have suitable climate. The characteristics of these helminthes are the adult worm is constant in digestion canal and the eggs with be infective when live in the ground, except Strogtloides stercoralis species. The life cycle of these species will be can if communities applied the healthy behavior, especially using foot barrier, permanent water closed, washing hand before eating, cutting and cleaning nail. Objective: to analyze differences about prevalence of soil transmitted helminthes infection based on daily behavior of elementary students. Method: This explanatory study used the us sectional design. The population study is the third class of elementary school students of Ungaran l, III, and VII (in urban) and Kawengen I and II Madrasah lbtidaiyah I and II (in rural), work area of Puskesmas Ungaran l. The number of samples is 162 students, choose randomly. The observed variables are soil transmitted helminthes infection, using permanent water closed, washing hand before eating, and nail cleaning. Data be analyzed by Chi Square test at the significant level 5%. Results: prevalence of STH infection in urban l4,8 % and in rural 65,43%, and also found 8 cases of cacing tambang. These are different Significantly base on using of permanent water closed and washing hand before eating habit (p<0, 05), and not significantly base on using foot barrier and nail cleaning habit (p>0,05). Conclusion: STH infection in rural higher than in urban, using permanent water closed and washing hands before eating will decrease prevalence of infection. Keyword: soil transmitted helminthes, foot barrier, washing hands, water closed